Conversion surgery for gastric cancer: current status and future perspectives - Itaru Yasufuku; Yusuke Okuma; Syunpei Tonomura; Seito Fujibayashi; Wakana Chikaishi; Masahide Endo; Yuji Hatanaka; Masahiro Fukada; Ryuichi Asai; Yuta Sato; Jesse Yu Tajima; Akitaka Makiyama; et al. (Japanese Journal of Clinical Oncology, 2026)
Abstract Conversion surgery, defined as surgical resection with curative intent after a favorable response to systemic chemotherapy in patients with initially unresectable gastric cancer, has attracted considerable attention as a potential treatment strategy for metastatic disease. Observational studies suggest that long-term survival may be achieved when R0 resection is accomplished. However, the therapeutic landscape has changed with advances in systemic treatment, including immune checkpoint inhibitor–based regimens. Recent evidence indicates that some patients who respond well to modern systemic therapies may achieve prolonged survival without surgery. Emerging observational data also suggest that, among patients with profound tumor regression or complete response to chemotherapy, overall survival may not differ substantially between those undergoing surgery and those continuing systemic therapy alone, raising important questions regarding the necessity of conversion surgery in current clinical practice. Accordingly, the Japanese Gastric Cancer Treatment Guidelines 2025 concluded that evidence remains insufficient to make a clear recommendation regarding conversion surgery. This review summarizes the concept and definition of conversion surgery, outlines the resectability classifications proposed by the Japan Clinical Oncology Group, and critically reviews evidence from observational studies and prospective trials, with particular attention to chemotherapy responders treated with or without surgery. In the modern treatment era, conversion surgery remains a promising approach; however, whether it offers a survival advantage over continued systemic chemotherapy has not been established. Clarification of its appropriate role in metastatic gastric cancer requires evidence from prospective randomized trials.